Challenging Therapy In Pregnant Woman With Systemic Lupus Erythematosus (SLE) and Chronic Hepatitis B - Choirina Windradi; Awalia Awalia (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease that attacks various body systems, especially in women of reproductive age. Therefore, patients who are planning a pregnancy or are pregnant need to assess the risk and predicts of disease activity during pregnancy. The most common complications of SLE in pregnancy are SLE disease activity, preterm delivery, preeclampsia and preganancy loss. Here, we report a pregnant SLE patient with co-infection hepatitis B. As the consequence of treated with immunosuppressant agent, both disease progression and immunosupressant agent can lead to severe infection. Furthermore, perinatal transmission is the most common form of transmission of hepatitis B. Finally, proper management could save mother and newborn.